Antara Kemandirian dan Keterasingan: Studi Fenomenologi Pengalaman Mahasiswa Menggunakan Ai Chatbot sebagai Media Pembelajaran - Nanda Puspita Aprianingrum; Rini Sugiarti; Ira Kusumawaty (KOLONI, 2026)
The rapid development of Artificial Intelligence (AI) has transformed the ways university students access information, understand academic content, and complete learning tasks. This study explores university students’ experiences of using AI chatbots in learning, focusing on the tension between independent learning and academic alienation. Employing a qualitative phenomenological approach, the study involved nine students from diverse academic disciplines and higher education institutions in Indonesia. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings indicate that AI chatbots function as accessible learning companions that support independent learning by providing immediate explanations, personalized feedback, academic guidance, and flexible access to information. Participants reported increased confidence, greater autonomy in learning, and improved efficiency in completing academic tasks. However, the findings also reveal a contrasting experience. Frequent reliance on AI encouraged shortcut-oriented learning practices, reduced engagement in deeper cognitive processes, and contributed to feelings of disconnection from learning activities, academic effort, and personal understanding. These experiences reflect a tension between the benefits of independent learning and the risk of academic alienation. Drawing on perspectives from educational psychology, educational technology, and higher education studies, this research highlights the dual role of AI chatbots in contemporary learning environments. The study emphasizes the importance of reflective and responsible AI use to ensure that technological support enhances, rather than diminishes, meaningful learning experiences.